2020
DOI: 10.1080/19336918.2020.1767489
|View full text |Cite
|
Sign up to set email alerts
|

The anti-cancer properties of heparin and its derivatives: a review and prospect

Abstract: Heparin, including unfractionated heparin (UFH), low-molecular-weight heparin (LMWH) and heparin derivatives, are commonly used in venous thromboembolism treatment and reportedly have beneficial effects on cancer survival. Heparin can affect the proliferation, adhesion, angiogenesis, migration and invasion of cancer cells via multiple mechanisms. The main mechanisms involve inhibition of heparanase, P-/L-selectin, angiogenesis, and interference with the CXCL12-CXCR4 axis. Here we summarize the current experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 78 publications
(95 reference statements)
1
57
0
2
Order By: Relevance
“…GAGs have been demonstrated to modulate numerous biological processes, ranging from embryonic development, regulation of enzymatic activities, extracellular matrix assembly, and ligand binding to receptors to the regulation of cell signaling, through the regulation of distinct proteins, such as growth factors, chemokines, and adhesion molecules ( Vallet et al, 2021 ). These processes are particularly important when related to diseases, including cardiovascular disease ( Wight, 2018 ), cancer ( Ma et al, 2020 ), infectious diseases ( Kamhi et al, 2013 ), neurodegenerative diseases ( Huynh et al, 2019 ), inflammatory responses ( Morla, 2019 ), and wound healing ( Salbach et al, 2012 ). A schematic representation of the structure of GAGs and their interactions with proteins and functions relevant to specific diseases is shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…GAGs have been demonstrated to modulate numerous biological processes, ranging from embryonic development, regulation of enzymatic activities, extracellular matrix assembly, and ligand binding to receptors to the regulation of cell signaling, through the regulation of distinct proteins, such as growth factors, chemokines, and adhesion molecules ( Vallet et al, 2021 ). These processes are particularly important when related to diseases, including cardiovascular disease ( Wight, 2018 ), cancer ( Ma et al, 2020 ), infectious diseases ( Kamhi et al, 2013 ), neurodegenerative diseases ( Huynh et al, 2019 ), inflammatory responses ( Morla, 2019 ), and wound healing ( Salbach et al, 2012 ). A schematic representation of the structure of GAGs and their interactions with proteins and functions relevant to specific diseases is shown in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“… 18 There are some pieces of evidence which suggest that heparin and heparinoids are involved in the suppression of cancer enhancement through serving the potent anti-cancer agent. 19 Heparin and these different types of GAGs are present in both extracellular and intracellular compartments of the cell. Heparin and associated different types of GAGs had been reported to accelerate the aggregation of various intracellularly existing peptide hormones.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to APAP overdose and I/R injury, heparin/HS are also found to reduce inflammation by lowering pro-inflammatory cytokines and maintaining ECM in CCL4-induced liver fibrosis [ 67 ], doxorubicin-induced liver damage [ 68 ], and primary graft dysfunction in liver transplantation [ 69 ]. Moreover, heparin/HS also have additional therapeutic potential for its antitumor, antivirus, and anti-hepcidin effects; reviews on these topics can be found elsewhere [ 70 , 71 , 72 , 73 ]. Briefly, heparin prevents tumor metastasis possibly by reducing adhesion, proliferation, and migration of cancer cells by targeting adhesion molecules (P-selectin, VCAM-1) or chemokines (CXCL12) in preclinical studies [ 71 ].…”
Section: The Potentials For Hs-based Therapeuticsmentioning
confidence: 99%
“…Moreover, heparin/HS also have additional therapeutic potential for its antitumor, antivirus, and anti-hepcidin effects; reviews on these topics can be found elsewhere [ 70 , 71 , 72 , 73 ]. Briefly, heparin prevents tumor metastasis possibly by reducing adhesion, proliferation, and migration of cancer cells by targeting adhesion molecules (P-selectin, VCAM-1) or chemokines (CXCL12) in preclinical studies [ 71 ]. However, the existing data in clinical trials does not support the antimetastatic effect of heparin [ 74 ].…”
Section: The Potentials For Hs-based Therapeuticsmentioning
confidence: 99%